Control interno y el desempeño laboral del área de personal de la Unidad de Gestión Educativa Local Contamana 2020 - Vasquez Vasquez, Juan Hernan (2022)
The general objective of the research was to determine the relationship between internal control and job performance of the Personnel Area of the Local Educational Management Unit of Contamana, 2020, using the type of study as descriptive - correlational and non-experimental design., which was made up of a population of 45 employees, who were surveyed through the survey and questionnaire. Therefore, the investigation concludes that the internal control is qualified as regular (27%) because the institution rarely has the strategic plan, and the objectives for the identification of risks, and sometimes they establish the procedure to develop the activities. of control, but the objectives for adequate control are never communicated to the inmate. For its part, job performance is rated as regular (27%) because the level of knowledge of their tasks is optimal, but the ability to execute productive ideas is regular. Likewise, in general, it was determined that internal control is significantly related to job performance with a correlation of 0.810 and significance at the 0.000 level.